2008
DOI: 10.1177/039463200802100221
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of Involvement ofChlamydia Pneumoniaein Lung Cancer by Means of Quantitative Real-Time Polymerase Chain Reaction

Abstract: Chlamydia pneumoniae, an obligate intracellular pathogen, is well-known as etiological agent of acute respiratory infections; the repeated or prolonged exposure to chlamydial antigens may promote the persistence of C. pneumoniae in the respiratory tract leading to chronic diseases, such as chronic obstructive pulmonary disease and asthma. The predilection of C. pneumoniae to cause respiratory tract infections combined with its persistent nature suggest that it might play a role in lung cancer. The aim of our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…Many clinical epidemiological studies analyzing the association between Cpn infection and the risk of lung cancer have been reported (Jackson et al, 2000;Koyi et al, 2001;Anttila et al, 2003;Kocazeybek, 2003;Littman et al, 2004;Littman et al, 2005;Chaturvedi et al, 2010), but no clear consensus has been reached (Koh et al, 2005;Sessa et al, 2008;Smith et al, 2008). This relationship was assessed more closely by performing a meta-analysis (Zhan et al, 2011) based on publications collected from electronic databases such as Pubmed, Embase, Web of Science, and CNKI.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical epidemiological studies analyzing the association between Cpn infection and the risk of lung cancer have been reported (Jackson et al, 2000;Koyi et al, 2001;Anttila et al, 2003;Kocazeybek, 2003;Littman et al, 2004;Littman et al, 2005;Chaturvedi et al, 2010), but no clear consensus has been reached (Koh et al, 2005;Sessa et al, 2008;Smith et al, 2008). This relationship was assessed more closely by performing a meta-analysis (Zhan et al, 2011) based on publications collected from electronic databases such as Pubmed, Embase, Web of Science, and CNKI.…”
Section: Discussionmentioning
confidence: 99%
“…The null association remained when limited to non-smokers (OR 1.01, 95% CI 0.55–1.83). However, a possible association among younger subjects aged 60 years and below could not be excluded (OR 1.70, 95% CI 0.79 –3.67) This study findings of a null association generally do not support the hypothesis that C. pneumoniae is independently associated with lung cancer among Chinese women, particularly in non-smokers Molecular-based investigation Sessa [ 18 ] An experimental study using lung biopsy specimens during surgery Investigated the presence of C. pneumoniae DNA in tumor lung tissues by using real-time PCR assay. Simultaneously, tumor and healthy tissues from the same patient with primary carcinoma lung were analyzed C. pneumoniae DNA was not detected in a single lung tumor tissue using a highly sensitive and specific real-time PCR assay based on FRET hybridization probes This study does not support C. pneumoniae in the pathogenesis of lung cancer, suggesting that further investigations are needed to clarify other potential causative factors for the development of this malignancy …”
Section: Resultsmentioning
confidence: 82%
“…Among the relevant literature, three case–control studies do not support the causal relationship between C. pneumoniae infection and lung cancer [ 18 20 ]. Out of three, one study looked for C. pneumoniae DNA by using PCR, while they failed to detect any [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, other studies [ 6 8 ] showed ORs of 1.2 to 2.8 after adjusting for smoking status, indicating that chronic Cpn infection is an independent risk factor for lung cancer. Several case-control studies showed that Cpn infection increased the risk of lung cancer development [ 10 – 13 , 16 ] but failed to show a correlation between serum Cpn antibodies and cancer risk [ 14 , 15 , 22 ].…”
Section: Discussionmentioning
confidence: 99%